Prosthetic valve sparing aortic root replacement—A persuasive option in well‐functioning aortic valve prosthesis. Issue 5 (2nd February 2021) - Idhrees, A. Mohammed; Velayudhan, Bashi V.; Jacob, Aju
Abstract: Objectives: Only limited data is available on prosthetic valve sparing aortic root replacement after aortic valve replacement. The aim of the present study was to assess the short‐ and midterm outcomes of the patients who underwent such procedures. Methods: From June 2004 to March 2018, 21 patients underwent this procedure. The mean age was 51.2 ± 10.2 years with a male predominance (85.7%). The mean time interval from aortic valve replacement to the present surgery was 10.62 years. Results: One patient died in immediate postoperative period who was taken up for emergency surgery—acute type A aortic dissection. Kaplan–Meier estimates of 1, 3, and 5 year survival were 95.2% ± 0.04%, 85.7% ± 0.07% and 85.7% ± 0.07%, respectively. No cardiac or aortic reinterventions were performed during follow up with a 100% freedom from reoperation at 5 years. Fifteen patients (71.43%) had aortopathy and had borderline pathology at the time of first surgery, with all of them having a tear either in the aortic sinuses or pervious aortotomy site. Conclusion: The favorable short and midterm results suggests that prosthetic valve sparing aortic root replacement is a valid option when possible. Utmost care has to be taken at the primary surgery especially in patients with aortopathy, trying to avoid the need for a second surgery.